Pelatihan Pengelolaan Emosi pada Anggota Bintara Remaja di Polresta Surakarta - Ima Nia Uliasari; Tiara Fadhilah Hasna Fadholi; Maya Desvira Riandy; Ella Putri Febria (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Teenage non-commissioned officers face several challenges in managing their emotions, which can hinder their ability to perform their duties optimally. One of the main challenges is lack of experience. As newcomers, young non-commissioned officers may not be used to dealing with various stressful, dangerous situations or involving interactions with the public. Emotion management training is expected to provide a number of important benefits for juvenile non-commissioned officers and the police institution as a whole. One of the main benefits is increased performance. To achieve the expected goals and benefits, the implementation of emotion management training must be carried out systematically and continuously. Training can begin with an introductory session on the importance of managing emotions, followed by practical training on communication skills, problem solving, and relaxation techniques. In addition, training should include simulations of real situations that youth NCOs may encounter, so that they can apply the skills learned in relevant contexts. Training evaluations must be carried out periodically to ensure that training objectives are achieved and the expected benefits can be felt. Evaluation can be done through knowledge tests, performance observations, and participant satisfaction surveys. Overall, this emotion management training provides short-term benefits in the form of reduced stress and improved performance, while also providing youth non-commissioned officers with skills that are crucial for their long-term careers in the police force. Thus, investment in the development of these skills not only improves operational efficiency but also supports the psychological well-being and professionalism of future police officers.